Mass uniformity of compounded powders divided into gelatin capsules - Monika Gajewska; Małgorzata Sznitowska; Marcin Płaczek (Polish Pharmaceutical Society, 2020)
Background Capsules are one of the most popular oral dosage forms compounded in a pharmacy. They are filled with pulverized active substance, often mixed with glucose or lactose as a diluting agent and filler. Gelatin empty capsules are available but in Polish pharmacies still starch capsules (cachets) are usually employed. Gelatin capsules are filled with powders by volume using dedicated hand-operated filling and closing apparatus, while cachets are hand-filled by weight, which is time-consuming. Polish pharmacists, unexperienced in using the first method, are not convinced that dividing the powders by volume is enough accurate. Aim of the study The aim of the study was to examine the distribution of the mass across individual gelatin capsules when the pharmacist employs a volumetric method. The effects of powder composition, capsule size, batch size and powder tamping on mass uniformity of compounded capsules were also investigated. Materials and methods Four homogeneous powders were prepared in a mortar: lactose, glucose and mixtures (1:1, v/v) of these excipients with drug substances acquired from tablets: furosemide (with lactose) and dienestrol (with glucose). Using a graduated cylinder, the specific volume of each powder was measured and then the powder was divided to 20 or 100 gelatin capsule shells by means of one of the hand-operated filling and closing apparatus: A or B, respectively. During the study 3 experiments were performed. In experiment I - placebo powders (glucose or lactose) were placed loosely in 20 capsules size 00, 0, 1, 2, 3 and in 100 capsules size 3 and 4. In a similar way the mixture of furosemide and lactose was divided to 100 capsules size 3 (experiment II). In experiment III lactose, glucose or mixture (1:1) of glucose with dienestrol were tightly packed to 100 capsules (size 3) using a tamper tool and apparatus B. All prepared capsules were analysed in terms of mass uniformity. Briefly, whole capsules were precisely weighed (± 1 mg) and from the mass of each capsule the mean mass of empty capsule with corresponding size was subtracted. The mass variability was assessed as calculated: mean, range, standard deviation, and relative standard deviation. Results The results of experiment I indicated that although bulk density of lactose and glucose differs, repeatability of the dosing process by volume is very good (RSD was <5% and only for the smallest capsule sizes, i.e. 3 and 4 it was higher than 3%). Similarly, low values of RSD (<3%) were obtained when the mixture of lactose and powdered tablets of furosemide was loosely placed in capsules (experiment II). The mass uniformity was in accordance with requirements, regardless the capsule size (00 - 4) and their number (20 or 100). Sometimes, in order to provide a correct dose, the pharmacist has to compress the powders in capsules using a special tamper tool. Results of the experiment III indicated that better mass uniformity was achieved for glucose comparing to lactose (RSD up to 4.7% and 8.0%, respectively). For compressed capsules, the pharmacopoeial (Polish Pharmacopoeia monograph "Pharmacy compounded medicines") uniformity limit was exceeded only for 6 out of the 300 capsules. It must be stated however that requirements for dose uniformity specified in the Ph. Eur. 2.9.5 monograph "Uniformity of mass of single-dose preparations" were not exceeded. Conclusions All tests performed during the study indicated that pharmacists can compound capsules using an accurate and less time-consuming volumetric method, with no concern regarding dose uniformity. Number of capsules, their size and composition of the powder have no influence on the dosing accuracy. However, if possible, pharmacists should avoid tamping of powders while filling the gelatin capsules.